Prokaryotic and eukaryotic community structure affected by the presence of an acid mine drainage from an abandoned gold mine - Bonilla, José Oscar (2018)
The acid mine drainage that originates in the abandoned gold mine in San Luis, Argentina, is released into La Carolina stream. The aim of this study was to determine the influence of this mine drainage on the physicochemical parameters of the area studied and on both prokaryotic and eukaryotic community structure. In addition, specific relationships between microbial taxonomic groups and physicochemical parameters were established. The drainage that flows into La Carolina stream acidifies the stream and increases its sulfate, Zn, Cd and Te concentrations. Microbial analysis showed that prokaryotic community structure is mainly affected by pH values. Actinobacteria and Gammaproteobacteria were abundant in samples characterized by low pH values, while Nitrospirae, Chloroflexi, Deltaproteobacteria, Thaumarchaeota and Euryarchaeota were associated with high concentrations of heavy metals. Otherwise, Alphaproteobacteria was present in samples taken in sunlit areas. Regarding eukaryotic community structure, the sunlight had the greatest impact. Inside the mine, in the absence of light, fungi and protists members were the most abundant microorganisms, while those samples taken in the presence of light displayed algae (green algae and diatoms) as the most abundant ones. After receiving the mine drainage, the stream showed a decrease in the diatom abundance and green algae predominated.